Genetically Engineered Brain Organoids Recapitulate Spatial and Developmental States of Glioblastoma Progression - Matthew Ishahak; Rowland H. Han; Devi Annamalai; Timothy Woodiwiss; Colin McCornack; Ryan T. Cleary; Patrick A. DeSouza; Xuan Qu; Sonika Dahiya; Albert H. Kim; Jeffrey R. Millman (Advanced Science)
Abstract Glioblastoma (GBM) is an aggressive form of brain cancer that is highly resistant to therapy due to significant intra‐tumoral heterogeneity. The lack of robust in vitro models to study early tumor progression has hindered the development of effective therapies. Here, this study develops engineered GBM organoids (eGBOs) harboring GBM subtype‐specific oncogenic mutations to investigate the underlying transcriptional regulation of tumor progression. Single‐cell and spatial transcriptomic analyses revealed that these mutations disrupt normal neurodevelopment gene regulatory networks resulting in changes in cellular composition and spatial organization. Upon xenotransplantation into immunodeficient mice, eGBOs form tumors that recapitulate the transcriptional and spatial landscape of human GBM samples. Integrative single‐cell trajectory analysis of both eGBO‐derived tumor cells and patient GBM samples reveal the dynamic gene expression changes in developmental cell states underlying tumor progression. This analysis of eGBOs provides an important validation of engineered cancer organoid models and demonstrates their utility as a model of GBM tumorigenesis for future preclinical development of therapeutics.